AN AYURVEDIC APPROACH IN THE MANAGEMENT OF TARUNYA PITIKA W.S.R. TO ACNE VULGARIS: A CASE STUDY - Amol, Velhal (International Journal of Ayurveda and Pharma Research, 2015)
In modern Era, physicians come across so many patients suffering from the disease Tarunya pitika. The incidence of Tarunya pitika is increasing day by day due to their fast lifestyle. Consumption of junk food, fast food, cold drinks leads to imbalances in Doshas which in turns affect body as well as mind. In Susrut samhita, Tarunya pitika is mentioned under Kshudra rogas. As per Modern science the symptoms of Tarunya pitika resembles Acne vulgaris. Acne is a chronic inflammatory disease of the pilo sebaceous units. Generally acne lesions appear at the places where sebaceous glands are naturally large and numerous as on Faces, Cheek, Neck, Back, Chest. All the dermatologists have considered Acne as the disease of sebaceous gland and it has cosmetological importance. Perfect skin is, for most people, a distant dream. Chronic skin conditions typically are not curable in western system of medicine, but they can be manageable using Ayurvedic therapies and by paying close attention to our lifestyle. This case is a example of Mukhadushika like skin disease can be managed with Ayurvedic therapy. The combination of certain Ayurvedic drug such as Arogyavardhini, Khadir, Daruharidra, Manjista etc is effective for the management of Tarunya pitika in the Dose of 2 gms. bid. Anupan: Luke warm water. Kala: Adhobhakt.